Relevancy of Online Classes in Mathematics Education - Badaila, Bishnu Bahadur (Journal of Lumbini Engineering College, 2023)
This research study entitled Relevancy of Online Classes in Mathematics Education was carried out to identify the views of students on relevance of online classes in mathematics education. The main objective of this study was to analyze student's barriers to online learning in mathematics education in the context of Nepal and to analyze the opportunities that students entertain while taking online class in mathematics education. The sample was 100 Students for questionnaire and 10 students for interview they were studying at first and fourth semesters of master degree in mathematics education during academic year 2077 at Tribhuvan University. The questionnaires and interview were used for the collection of data containing close-ended and open ended questions. The Campus and the students were selected by using probability proportional sampling procedure. The collected data were analyzed by descriptively and statistically. In the conclusion the opportunities of online class outweigh the barriers that students face. Online class provides great opportunity for universities in developing countries to improve their teaching and learning processes. Moreover, the findings of this study states that master level students of mathematics education had positive opinion towards the online classes in mathematics education. From all the finding the researcher concludes that online class is relevant for the students of mathematics education in Tribhuvan University.